2022
DOI: 10.1371/journal.pone.0262124
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost electrochemical detection of arsenic in the groundwater of Guanajuato state, central Mexico using an open-source potentiostat

Abstract: Arsenic is a carcinogenic groundwater contaminant that is toxic even at the parts-per-billion (ppb) level and its on-site determination remains challenging. Colorimetric test strips, though cheap and widely used, often fail to give reliable quantitative data. On the other hand, electrochemical detection is sensitive and accurate but considerably more expensive at the onset. Here, we present a study on arsenic detection in groundwater using a low-cost, open-source potentiostat based on Arduino technology. We te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…By identifying these factors, targeted investigations and interventions can be implemented to improve water quality in affected communities. Effective and cheap monitoring practices are critical for this purpose, and previous studies in Mexico, Bangladesh, and other regions of the US have demonstrated the efficacy of using portable field testing kits to measure arsenic in drinking water [ 80 , 81 , 82 ]. Adopting this approach on a frequent and periodic basis can help overcome challenges related to seasonality and timing of sampling, and enable the rapid dissemination of results to affected communities.…”
Section: Discussionmentioning
confidence: 99%
“…By identifying these factors, targeted investigations and interventions can be implemented to improve water quality in affected communities. Effective and cheap monitoring practices are critical for this purpose, and previous studies in Mexico, Bangladesh, and other regions of the US have demonstrated the efficacy of using portable field testing kits to measure arsenic in drinking water [ 80 , 81 , 82 ]. Adopting this approach on a frequent and periodic basis can help overcome challenges related to seasonality and timing of sampling, and enable the rapid dissemination of results to affected communities.…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of As(III) and total As were determined using anodic stripping voltammetry (ASV) and a method based upon established procedures, [76,79,80] described in detail in Supporting Information section 1.8. Oxidation progress was monitored using [As(III) (aq)] rather than [As(V) (aq)] as this is expected to give a more accurate measure of oxidation kinetics, especially at low total arsenic concentrations [81] .…”
Section: Methodsmentioning
confidence: 99%
“…However, the pricey, hefty, and elegant instrumentation, the time-consuming, expensive, and labor-intensive analytical procedures, and the need for well-established laboratory setups render these analytical techniques rather ineffective for quick and on-site sensing of arsenic. , Therefore, intense research efforts are currently being invested in developing rapid, simple, reliable, pocket, and environment-friendly approaches for the detection/analysis of As, with electrochemical methods emerging as the front-runners . The electrochemical methods of analysis have the advantage of being rapid and cost- and time-effective, and they may be used to detect very low concentrations of arsenic with good selectivity, sensitivity and, reliability. Additionally, these methods require a simple, safe, and easy-to-operate instrumentation that can be miniaturized into battery-powered automatic setups for on-site arsenic analysis, ideal for remote places and countries with insufficient infrastructure and technical facilities . However, the unavailability of economical but electrochemically stable, redox-selective electrode materials with high activity and outstanding electron transport capabilities continues to hamper the development of such arsenic-sensing electrochemical devices.…”
Section: Introductionmentioning
confidence: 99%
“…12−15 Additionally, these methods require a simple, safe, and easy-to-operate instrumentation that can be miniaturized into battery-powered automatic setups for on-site arsenic analysis, ideal for remote places and countries with insufficient infrastructure and technical facilities. 16 However, the unavailability of economical but electrochemically stable, redox-selective electrode materials with high activity and outstanding electron transport capabilities continues to hamper the development of such arsenic-sensing electrochemical devices. To date, the potential utility of a diverse range of materials, including bulk/ nanophase phase metals and other materials such as carbon nanoparticles, noble MNPs, metal oxide nanoparticles, and bimetallic nanoparticles including biomaterial-modified electrodes, for the electrochemical sensing of arsenic has been tested.…”
Section: ■ Introductionmentioning
confidence: 99%